Knowledge, attitude, and practices related to antibiotic use and resistance among the general public of coastal south Karnataka, India - A cross-sectional survey - Khyati Bhardwaj; Suchitra Shenoy M; Shrikala Baliga; B. Unnikrishnan; B. Shantharam Baliga (Elsevier, 2021)
Background: The study was performed to understand the knowledge, attitude, and practices of community towards antibiotic use and resistance. Methods: The data was collected from 515 participants from the general public with a pre-tested, validated, Likert-scale based self-administered questionnaire. The questionnaires were distributed to the participants selected randomly from the five administrative subdivisions of the Dakshina Kannada District. Results: The response rate was 84.85%. Respondents were unaware of the action of antibiotics with 49% stating that antibiotics kill viruses. Also, there were misconceptions about antibiotic resistance with 52% stating humans become resistant to antibiotics. Appropriate attitude towards buying antibiotics with a prescription was shown by 67% of the respondents. Antibiotics for cold were used by 45% of the respondents. Conclusion: Most of the people had fairly appropriate attitude towards accessing antibiotics but there are misconceptions regarding antibiotic use and effects. Knowledge regarding antibiotic resistance and its causes is limited. The focus in future should be on creating awareness among the public on the prudent use of antibiotics.